Exchange Interactions Drive Supramolecular Chiral Induction in Polyaniline (Small Methods 10/2020). Issue 10 (7th October 2020) - Mishra, Suryakant; Kumar, Anup; Venkatesan, Munuswamy; Pigani, Laura; Pasquali, Luca; Fontanesi, Claudio
Abstract : In article number 2000617, Claudio Fontanesi and co‐workers study the camphor sulfonic acid induction of chirality on the supermolecular structure of electropolymerized aniline. The emergence of chirality is also associated to spin filtering properties of the chiral polymer, revealed by conducting probe atomic force microscopy in the presence of a magnetic field. Theoretical results suggest that the chiral induction is due to exchange interaction energy.